INTEGRATING HOTS IN INDONESIAN HIGH SCHOOL TEXTBOOKS: A COMPARATIVE STUDY OF THE 2013 AND MERDEKA CURRICULUM - Abd Rahim; Abdul Aziz; Ilma Rahim; Rizki Herdiani; Jenri Ambarita; Nurhikmah (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
This study evaluates and compares the integration of Higher Order Thinking Skills (HOTS) in Indonesian language textbooks for high school students under the 2013 Curriculum and the Merdeka Curriculum. Using a qualitative descriptive approach, the study conducts content analysis of four textbooks two aligned with the 2013 Curriculum and two with the Merdeka Curriculum employing HOTS criteria derived from Bloom’s taxonomy. The findings reveal that the 2013 Curriculum textbook (2014 edition) includes 78 questions, with 17 in the analyzing category and 37 in the evaluating category (32 checking and 24 criticizing questions). In comparison, the Merdeka Curriculum textbook (2021 edition) presents 55 questions, comprising 14 analyzing and 32 evaluating questions (25 checking and 16 criticizing). Despite a decrease in the total number of questions, the Merdeka Curriculum exhibits a greater emphasis on deeper critical evaluation, reflecting a pedagogical shift toward fostering students' critical thinking competencies. The contribution of this research lies in providing empirical evidence on how curriculum reforms affect the cognitive depth of textbook content, thereby offering insights for curriculum developers, textbook authors, and educators in designing learning materials that effectively promote 21st-century skills.